Genetic Structure and Eco-Geographical Differentiation of Cultivated Keng Rice (Oryza sativa L. subsp. japonica) in China Revealed by Microsatellites - Dong-ling ZHANG (Journal of Integrative Agriculture, 2012)
China is one of the largest centers of genetic diversity of Oryza sativa L. and is the original centers of Oryza sativa L. subspecies japonica. Using a genetically representative core collection of 1 442 rice landraces of japonica in China, the genetic structure, differentiation, and geographic diversity were analyzed. The model-based structure analysis on varieties within three ecotypes revealed 16 eco-geographical types, which are partially accorded with some of the ecological zones in China. The differentiation of eco-geographical types contributed to the local ecological adaption and physical isolation, and maybe could be used to develop the heterotic groups of japonica. To facilitate the identification of different ecotypes and eco-geographical types, we provided the SSR character alleles of each ecotype or geographical eco-group and a rapid discriminated method based on these character alleles. Lastly, investigation on genetic diversity, genetic differentiation indicated that southwest region of China, including south of Yunnan Province, northwest of Guangxi Zhuang Autonomous Region, and southwest of Guizhou Province, possessed the highest genetic diversity and all the necessary conditions as a center of genetic diversity and should be the center of genetic diversity of rice landraces of japonica in China.